The Effect of the Use of Technology-Based Learning Media and Teacher Self-Efficacy on Elementary School Teachers' Performance in Tanjung Lago District - Mujiyanto; Syaiful Eddy; Muhammad Juliansyah Putra (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2026)
Although previous studies have reported positive relationships between technology use, teacher self-efficacy, and teacher performance, limited evidence has explored their combined contribution from an educational management perspective, particularly in rural elementary schools. This study examines the influence of technology-based learning media and teacher self-efficacy on the performance of elementary school teachers in Tanjung Lago District, Indonesia. Using a quantitative explanatory survey, data were collected from 82 teachers selected through proportional random sampling and analyzed using multiple linear regression in IBM SPSS Statistics 26. The results show that both technology-based learning media and teacher self-efficacy significantly and positively influence teacher performance. The regression model explains 74.0% of the variance in teacher performance (R² = 0.740), with technology-based learning media identified as the stronger predictor. These findings highlight the complementary role of digital resources and teachers’ psychological capacity in enhancing performance and suggest that educational leaders should strengthen ICT infrastructure, professional development, and self-efficacy support to improve instructional quality.